Quantitative proteomic analysis of iron-regulated outer membrane proteins in Aeromonas hydrophila as potential vaccine candidates. Issue 68 (September 2017) - Wang, Yuqian; Chen, Huarong; Guo, Zhuang; Sun, Lina; Fu, Yuying; Li, Tao; Lin, Wenxiong; Lin, Xiangmin
Abstract: The iron-regulated outer membrane protein (OMP) of Aeromonas hydrophila is an effective vaccine candidate, but its intrinsic functional components are largely unknown. In this study, we compared the differentially expressed sarcosine-insoluble fractions of A. hydrophila in iron-limited and normal medium using tandem mass tag labeling-based quantitative proteomics, and identified 91 upregulated proteins including 21 OMPs and 83 downregulated proteins including 10 OMPs. Subsequent bioinformatics analysis showed that iron chelate transport-related proteins were enriched in increasing abundance, whereas oxidoreductase activity and translation-related proteins were significantly enriched in decreasing abundance. The proteomics results were further validated in selected altered proteins by Western blotting. Finally, the vaccine efficacy of five iron-related recombinant OMPs (A0KGW8, A0KFG8, A0KQ46, A0KIU8, and A0KQZ1) that were increased abundance in iron-limited medium, were evaluated when challenged with virulent A. hydrophila against zebrafish, suggesting that these proteins had highly efficient immunoprotectivity. Our results indicate that quantitative proteomics combined with evaluation of vaccine efficacy is an effective strategy for screening novel recombinant antigens for vaccine development. Highlights: OMP fractions were compared to iron limited condition using proteomics method. 21 upregulated and 10 down regulated OMPs were identified. Selected iron-regulated OMPs were validated by western blotting. At less five iron-regulated OMPs have highly efficient immunoprotectivity.